Analisis Pengaruh Lingkungan Kerja Dan Kompensasi Terhadap Kinerja Pegawai Yang Dimediasi Oleh Kepuasan Kerja - Rumengan, Reza Juno (Universitas Sam Ratulangi, 2018)
The purpose of this study was determine to the effect of work environment, compensation, job satisfaction and employee performance in economic and business faculty of sam ratulangi university. This study used quantitative research models of associative. Results showed that the work environment does not significantly influence on satisfaction. Compensation with mediating job satisfaction has a significant influence on job satisfaction and employee performance in economic and business faculty of sam ratulangi universityKeywords: Work environment, compensation, job satisfaction and employee performance